Fecal Elastase Levels Predict Honeycombing in Pancreas Detected with Endoscopic Ultrasound - Sinan Akay; Burcu Şirin; Belkıs Ünsal (Canadian Journal of Gastroenterology and Hepatology)
Background and Study Aims. We aimed to demonstrate the association between fecal elastase levels and Rosemont categories in patients with chronic changes in pancreas detected with endoscopic ultrasound. Patients and Methods. Patients were selected consecutively from endosonography examinations performed for upper gastrointestinal subepithelial lesions and for pancreas evaluation. Pancreas imaging findings were categorized according to the Rosemont criteria using echoendoscope. Patients who were indeterminate of, suggestive of, and consistent with chronic pancreatitis were included in the study. Fecal elastase measurements were performed after the patients were qualified to participate in the study according to endosonography findings. Results. Seventy patients were included in the study. 54 of them were male. Mean age of the patients was 51.7 ± 10.2 year. There were 36 patients in the indetermine group for chronic pancreatitis. Mean fecal elastase level was 507.1 ± 14.6 μg/g in the indeterminate group. There were 24 patients in the suggestive group of chronic pancreatitis. Mean fecal elastase level was 400.4 ± 121.4 μg/g in the suggestive group of chronic pancreatitis. There were 10 patients, in the consistent group with chronic pancreatitis. Mean fecal elastase level was 134.8 ± 86.1. The difference between the three groups of fecal elastase values was statistically significant compared with Kruskal Wallis test. Ordinal logistic regression analysis showed that there was a significant relation between endosonografic categories and fecal elastase values with Nagelkerke value of 0.704. Conclusions. Fecal elastase levels of each of the endosonographic categories were significantly different from each other. Also, fecal elastase values can predict chronic changes in pancreas detected with endoscopic ultrasound.